Quality of life after laparoscopic removal of Essure® sterilization devices - Gautier Chene; Emanuele Cerruto; Stephanie Moret; Karine Lebail-Carval; Philippe Chabert; Georges Mellier; Erdogan Nohuz; Gery Lamblin; T. Justin Clark (Elsevier, 2019)
Objective(s): To assess changes in quality of life after laparoscopic removal of Essure® sterilization devices (Bayer AG, Leverkusen, Germany). Study Design: In this prospective observational study in an academic research hospital, 80 women with new or worsening symptoms since placement of Essure® sterilization devices undergoing subsequent surgical removal were included. Laparoscopic removal of Essure® devices and salpingectomy with or without cornual excision were performed. Concomitant uterine procedures could be associated where indicated for gynaecological complaints. Comparison using the T student test for coupled series was done in this before-and-after study. Results: Health related quality of life (HRQL) was the primary outcome measured by the Short Form 12 (SF-12) questionnaire and a global 10 cm visual analogue scale (VAS). Secondary outcomes included assessment of pain, using continuous (VAS) and ordinal scales (Modified McGill Pain Questionnaire), menstrual bleeding (pictorial blood loss assessment chart (PBAC) score) and surgical feasibility and safety. There was a significant improvement in quality of life in both mental and physical health aspects of the SF-12 (34.02 (+/−1.19) vs. 49.61 (+/−1.42, P < .0001) and 36.55 (+/−0.99) vs. 43.32 (+/−1.18, P < .0001 respectively) as well as global VAS assessment (+2.91 (SD +/−0.27)) at the end of the first post-operative month. These improvements were maintained at three and six months. Mean pain decreased at one month following surgery compared to baseline (VAS 3.6 (+/−0.36) to 1.4 (+/−0.25), P < .0001 and McGill pain score 18.70 (+/−1.88) to 4.73 (+/−0.90), P < .0001). Improvements of a similar magnitude were observed when analysis was restricted to the 47 women without concomitant uterine surgery. No significant changes in bleeding were seen following of Essure® device removal. Planned procedures were all successfully completed. Conclusion: Laparoscopic removal of Essure® devices in symptomatic women is technically successful and associated with short and medium-term improvement in quality of life as well as reduction in pelvic pain. Keywords: Essure® removal, Hysteroscopic sterilization, Laparoscopy, Quality of life, Salpingectomy